2007
DOI: 10.1002/adma.200700904
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Electrolytic Switching in Phase‐Change Chalcogenide Films

Abstract: This Communication presents the important finding that certain chalcogenide materials, well-known from rewritable optical recording, allow resistive memory states that are a combination of two electrically-induced (reversible) switching processes, i.e., an actual amorphous-crystalline phase transformation and a (electrolytic) polarity-dependent resistance change. Nanometer-sized crystalline marks were written electrically in amorphous Ge 2 Sb 2+x Te 5 films using atomic force microscopy (AFM), and their resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
4
50
0
Order By: Relevance
“…A detailed investigation of the influence of electron beam on the crystal growth is subject of a separate publication. 38 In order to entirely avoid such an influence in the present experiments, crystallization was carried out without electron beam exposure for fixed time intervals at elevated temperature. After each interval, the sample is cooled to nearly room temperature ͑below 30°C͒ for TEM measurements, i.e., the measurements of nucleation and growth were made in discrete heating and cooling steps unlike in our previous studies, 35,36 where it was done in a more or less continuous manner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed investigation of the influence of electron beam on the crystal growth is subject of a separate publication. 38 In order to entirely avoid such an influence in the present experiments, crystallization was carried out without electron beam exposure for fixed time intervals at elevated temperature. After each interval, the sample is cooled to nearly room temperature ͑below 30°C͒ for TEM measurements, i.e., the measurements of nucleation and growth were made in discrete heating and cooling steps unlike in our previous studies, 35,36 where it was done in a more or less continuous manner.…”
Section: Methodsmentioning
confidence: 99%
“…37 In the following we will disregard this effect, but we will address it in Ref. 38 where also the influence of electron beam of the TEM ͑that is now absent for the present measurements͒ on the growth velocity is analyzed in detail.…”
Section: A Growth Propertiesmentioning
confidence: 99%
“…Many research groups have reported various types of recording methods based on scanning tunneling microscopy (STM) [4,5], atomic force microscopy (AFM) [6][7][8][9][10], and scanning near-field optical microscopy (SNOM) [11,12], etc. Moreover, in order to increase the data transfer rate, parallel data processing using a probe array, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 128.192.114 19. Downloaded on 2015-06-28 to IP…”
mentioning
confidence: 98%